Perkembangan Motif, Makna, dan Fungsi Tato Di Kalangan Narapidana dan Tahanan di Yogyakarta - Handoko, Cons. Tri (Makara Human Behavior Studies in Asia, 2010)
This article describes about the developments of the motifs, meaning, and functions of the tattoo among the convicts and detainees in Yogyakarta since 1950s. The research respondents were the convicts and detainees in the Socialization Institution of Class IIA Yogyakarta, ex-convicts, and tattoo artists who understood about the developments of tattooing in Yogyakarta. The Motifs of tattoo among the convicts and detainees were flora, fauna, people portraits, horror, tribal tattoo, heart iconics, typography, biohazard and biomechanical, also still life. There were two appearances of the motif, standed alone and mix motifs. Each motif had particular meaning. The tattoing technique used simple equipment as wool, needle, and norit (a brand of stomach-ache medicine) and mechanical tattoo machine. Tattoo and tattooing activities among the convicts consist of two major functions, individual and social. As individual function, tattoo is an artwork. In this term, tattoo has a function as the expression of experiences, included as a reminder of specific experiences and body decoration. Others as a religious expression, therapy and relaxation, talisman, sex appeal, selfprotection and to cover up the wounds and other tattoo which were not good. Another individual function was job opportunity for anyone who had ability in tattoing. The social function of tattoo was as a group symbol, a medium of socialization and enhancing individual self-confidence in the group either inside or outside the Socialization Institution.